Effectiveness of Self-Instructional Module on Knowledge and Practices Regarding Infection Control Strategies in Maternity Department Among the Staff Nurses Working in Selected Hospitals of Hisar - ., Vandana (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2023)
Healthcare providers are persistently exposed to disease-causing organisms. Many of which can cause serious infections or health problems. Therefore, nurses should have profound knowledge regarding infection control. Objective: To assess the level of knowledge and practice regarding infection control strategies among staff nurses working in the maternity department. Material and methods: The study was conducted at Adhar hospital, Hisar. It is a super speciality hospital with a bed strength of over 100, which have a comprehensive emergency department, which provides medical, trauma and surgical emergency services. The study population covers all the staff nurses in the maternity department. A convenient sampling technique was used and six staff nurses were selected by convenient sampling each day. The tools developed for data collection included a semi-structured questionnaire and checklist which contained two parts, items in Part-A related to patients’ demographic characteristics such as age, sex, education qualification etc. Part B contains multiple choice questions and a checklist for the assessment of knowledge and practices. The tool was validated by experts from the field of nursing. An informational SIM was prepared to improve the knowledge of the staff nurses. It consists of the basic concept of infection, universal precautions, Labour room cleaning and biomedical waste management. Data collection was done after seeking permission from the Ethics Committee of Aadhar Hospital. Every day five staff nurses in the maternity department were selected. Informed written consent was obtained from each staff member and informational verbal consent was obtained from each nurse involved in the study. Data were analyzed using descriptive and inferential statistics. Results: In the pre-test, 3.3% of staff nurses have adequate knowledge, 63.3%% have moderate knowledge, 33.3 % of staff nurses have inadequate knowledge, and in the post-test 19(31.6%) have moderate knowledge and left 41 (68.3) have adequate knowledge. However, the majority of staff nurses have moderate knowledge regarding infection control strategies. In the pre-test, we had a total of 60 participants out of which 59 (98.3%) participants were having unhealthy practices and the remaining 1 (1.6%) participant was having healthy practices. In the post-test rest of the total 60 participants, 36 (60%) participants were having unhealthy practices and the rest 24(40%) had healthy practices. Comparison of overall pre-test and post-test sore depicts that during the pre-test staff, nurses have less knowledge regarding infection but after post-test result shows the effectiveness of the SIM. Conclusion: The present study concluded that this study can be helpful to staff nurses in understanding the relationship between infection control strategies and reducing maternal mortality and morbidity. With the help of this study, researchers can conduct more studies on infection and infection control in the maternity department.